Enhancing the Nutritional Profile of Noodles With Bambara Groundnut (Vigna subterranea) and Moringa (Moringa oleifera): A Food System Approach - Hussin, Hilda; Gregory, Peter J.; Julkifle, Advina L.; Sethuraman, Gomathy; Tan, Xin Lin; Razi, Fadhil; Azam-Ali, Sayed N. (Frontiers in Sustainable Food Systems, 2020)
Bambara groundnut (BG, Vigna subterranea) and moringa (Moringa oleifera) are underutilized crops that improve nutritional quality of diets locally. The objectives of this study were to measure the performance of both crops on a marginal soil, analyze the harvested plant parts and noodles produced from them, and to undertake taste testing and survey consumer reactions. The noodles contained either 100% wheat flour or wheat with either BG flour (20%) or moringa powder (6%). BG yielded 0.70 t ha−1 of dry nuts and moringa 1.54 t ha−1 of dry leaflets. Both plant products were high in nutrients (especially K, and Ca in moringa) and some amino acids. Inclusion in noodles significantly enhanced their nutritional composition particularly energy content, crude fat, crude fiber and carbohydrate. Significant increases (p < 0.05) of Mg, Mn, P, K, and Zn occurred. Total essential amino acid concentration increased from 34.1% in the pure wheat noodles to 38.2% in BG and 34.8% in moringa noodles. Sensory analysis showed acceptability of all three noodle types was above the “Neither like nor dislike” category leaning toward the liking end for almost all the attributes tested. A consumer reaction survey showed there were internal and external factors motivating respondents to choose both products. Weak correlations were found between some of these factors and respondents' willingness to pay more for the BG and moringa noodles. We conclude that adopting a comprehensive research approach from plant to plate can assist transfer of underutilized crops from field studies to acceptable consumer products with enhanced nutritional profiles.